Spontaneous Uterine Rupture of an Unscarred Uterus before Labour - Mamour Guèye; Magatte Mbaye; Mame Diarra Ndiaye-Guèye; Serigne Modou Kane-Guèye; Abdoul Aziz Diouf; Mouhamadou Mansour Niang; Hannegret Diaw; Jean Charles Moreau (Case Reports in Obstetrics and Gynecology)
Uterine rupture is a public health problem in developing countries. When it is spontaneous, it occurs most often during labor in a context of scarred uterus. Uterine rupture during pregnancy is a rare situation. The diagnosis is not always obvious and morbidity and maternal and fetal mortality is still high. We report a case of spontaneous uterine rupture during pregnancy at 35 weeks of an unscarred uterus before labour. This is an exceptional case that we observe for the first time in our unit.